High prevalence of low-concentration antimicrobial residues in commercial fish: A public health concern in Bangladesh. - Md Raihan Khan Nayem; Md Rahim Badsha; Md Kaisar Rahman; Shahneaz Ali Khan; Md Mazharul Islam; Md Latiful Bari; John I Alawneh; Ricardo J Soares Magalhaes; Mohammad Mahmudul Hassan (PLoS ONE)
Antibiotics are widely used in commercial fish farms in Bangladesh for therapeutic and prophylactic purpose, raising concerns about antimicrobial resistance (AMR) and environmental contamination. This study used Thin Layer Chromatography to detect antimicrobial residues in four commercially available fish species- Tilapia (Oreochromis aureus), Stinging catfish (Heteropneustes fossilis), Climbing perch (Anabas testudineus), and Pabda (Ompok pabda)-with 100 samples per species. Ultra High-Performance Liquid Chromatography quantified residues in a subset of 25 samples per species. The prevalence of Ciprofloxacin, Oxytetracycline, and Chlortetracycline residues varied significantly among fish species, with the highest prevalence observed for Ciprofloxacin in Tilapia (42%), Oxytetracycline in Pabda (41%), and Chlortetracycline in Tilapia (49%). Additionally, the prevalence of Levofloxacin and Chlortetracycline differed by sampling location, with the highest levels found in Jhawtala market, 27.5% for Levofloxacin and 53.8% for Chlortetracycline. Furthermore, residue concentrations were highest for Enrofloxacin in Climbing perch (69.32 µg/Kg) and Oxytetracycline in Pabda (88.73 µg/Kg). The highest Hazard Quotient (HQ) was for Enrofloxacin in Climbing perch (0.480), followed by Pabda (0.460), Stinging catfish (0.420), and Tilapia (0.387). While the HQ values were below 1.0, indicating no immediate toxicological risk, residues raise public health concerns due to the chance of potential AMR development. Further research is needed on antimicrobial bioaccumulation, indirect exposure sources, environmental contamination, and antimicrobial resistance in aquaculture and wild fish.